1st Grade Children's Beginning Reading Learning Using AISM Media - Irianto, Wawan (International Proceedings of Nusantara Raya, 2023)
This research is qualitative descriptive research. The aim of the research is to find out the process of learning to read beginning in class 1 at MI An-Nuur Karangtawang, Nusawungu District, Cilacap Regency for the 2022/2023 academic year. This research is based on the importance of reading learning media for grade 1 elementary students. Data collection techniques were obtained by observations, interviews, and documentation. The subjects of this study were 1st grade students, a total of 44 children who were divided into 2 study groups. From the results of observations, interviews, and documentation, the researcher obtained that MI An-Nuur Karangtawang had used AISM as a reading learning media. This media is a sylable reading method. AISM stands for Anak Islam Suka Membaca (Islamic Students Like to Read). This media is beeing used as a mandatory learning book for grade 1 students at MI An-Nuur Karangtawang since 2013. In the 2022/2023 school year the number of students in grade 1 was 44. Beginning reading learning with AISM media begins a week after the orientation period for new students. During the first 6 months, researcher obtained data that 9 children were able to read simple paragraphs, 25 children were able to read simple sentences, 10 children read haltingly. In the 10th month there are 20 children who are able to read paragraphs, 20 children are able to read simple sentences, 4 children read haltingly. The results of this study indicates that the AISM media is effective enough and very efficient for teaching and learning to read at the beginning of grade 1 at MI An-Nuur Karangtawang Nusawungu Cilacap.